Same Services New Operations in the Face of Challenges: The Impact on Library Services at the University of Guyana - Lowe, Debra; Rose, Simmone La; Harris, Clyden (Advances in Social Sciences Research Journal, 2024)
The COVID-19 pandemic forced the University of Guyana to close its physical campuses on March 16, 2020. This closure affected the predominantly manual operations of the university. This study examines the impact of the COVID 19 pandemic on the University of Guyana Library, providing a synopsis of some of the issues encountered during the period and how they were addressed. A case study approach was used to investigate the phenomenon. The methodology used for collecting and analyzing the data was qualitative and descriptive in nature, adapting the purposive sampling technique. A questionnaire was used to elicit responses from key library personnel who were actively involved in managing the library during the pandemic. Data was also gathered from participatory observations. The results indicated that against all odds, the library adapted its services using various initiatives to continue serving its patrons, and conducted aspects of library administrative work in order to identify deficiencies for future strengthening and enhancement in preparation for a blended mode of operation.